La Acrópolis de Chilonché (Guatemala): Crónica de las investigaciones de un patrimonio en riesgo en el área maya - Gaspar Muñoz Cosme; Cristina Vidal Lorenzo; Alessandro Merlo (Restauro Archeologico, 2016)
Intensive research carried out at the Acropolis of the ancient Mayan city of Chilonché, which begun as a result of the fortuitous discovery in 2009 of a large zoomorphic sculpture hidden inside its basement, has revealed the great quality of its buildings, one of which retains an exceptional room decorated with murals, which was closed by the Mayas themselves at the end of the Classical period. However, the widespread archaeological looting to which the Acropolis has been subjected has greatly hampered the work of research and conservation on this remarkable cultural heritage. In this regard, the application of new documentation technologies through the use of the laser scanner and the later treatment of the information for the use of 3D techniques has allowed a detailed analysis which will help to ensure their appropriate preservation.